2020
DOI: 10.1007/s42452-020-03677-z
|View full text |Cite
|
Sign up to set email alerts
|

Selection of basalt fiber with resistance to concrete alkaline environment

Abstract: Due to a growing interest in basalt fibers as a reinforcing material for concrete, it becomes necessary to study behavior of such fibers and their interaction with the concrete matrix. Basalt fibers have prospective mechanical and processability properties, as well as good cost-effectiveness when used as concrete reinforcement. However, alkali resistance properties of basalt fiber are rather weak. Three types of basalt fibers from various manufacturers are presented, which were produced from different basalt r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
5
0
1

Year Published

2021
2021
2023
2023

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 11 publications
(9 citation statements)
references
References 34 publications
0
5
0
1
Order By: Relevance
“…The surface roughness of the sample is assumed to be atomic-flat, not influencing the EDS analysis. We employed a typical composition of basalt-derived glass fibre, as reported by [41][42][43], whose chemical composition, expressed as the mass fraction of oxides, is reported in Table 1, with a mass density 2.66 g/cm 3 [41,44,45]. Basalt fibres are produced by melting volcanic basalt rocks at 1450-1500 • C at atmospheric pressure into a furnace, and forcing the molten material through platinum/rhodium crucible bushings to create fibres (see [7] for details of the process).…”
Section: Fibre-reinforced Geopolymer Modelmentioning
confidence: 99%
“…The surface roughness of the sample is assumed to be atomic-flat, not influencing the EDS analysis. We employed a typical composition of basalt-derived glass fibre, as reported by [41][42][43], whose chemical composition, expressed as the mass fraction of oxides, is reported in Table 1, with a mass density 2.66 g/cm 3 [41,44,45]. Basalt fibres are produced by melting volcanic basalt rocks at 1450-1500 • C at atmospheric pressure into a furnace, and forcing the molten material through platinum/rhodium crucible bushings to create fibres (see [7] for details of the process).…”
Section: Fibre-reinforced Geopolymer Modelmentioning
confidence: 99%
“…Basalt fiber filaments, especially those with high modulus, high strength, and high temperature resistance are characterized by high stiffness; the properties usually used in aerospace; nevertheless, basalt fibers have a prickly sensation owing to their high rigidity and are prone to splitting under twisting (Chen et al, 2017;Pastsuk et al, 2020). Organic staple fibers, such as cotton, tencel, and viscose, normally have a low modulus as well as high spinnability and comfort (Karthik et al, 2017;Goergen et al, 2020).…”
Section: Introductionmentioning
confidence: 99%
“…In terms of economy, environmental protection, and reinforcement effect, after a large number of studies and comparisons [ 20 , 21 , 22 , 23 ], it has been found that polypropylene fibers, glass fibers, polyvinyl alcohol fibers, and basalt fibers are currently among the most frequently used fibers. Therefore, taking different fiber types (polypropylene fiber, glass fiber, polyvinyl alcohol fiber, and basalt fiber) and fiber lengths (3, 6, 9, and 12 mm) as the research objects for indoor tests and through comprehensive analysis of various physical and mechanical parameters, the influence mechanism of fiber length and fiber type on the strength of microbial solidified sand soil is explored.…”
Section: Introductionmentioning
confidence: 99%